2017
DOI: 10.1016/j.neuroimage.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive ability correlates with hippocampal and prefrontal microstructure

Abstract: The ability to introspectively evaluate our experiences to form accurate metacognitive beliefs, or insight, is an essential component of decision-making. Previous research suggests individuals vary substantially in their level of insight, and that this variation is related to brain volume and function, particularly in the anterior prefrontal cortex (aPFC). However, the neurobiological mechanisms underlying these effects are unclear, as qualitative, macroscopic measures such as brain volume can be related to a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 72 publications
12
96
1
2
Order By: Relevance
“…Previous studies have consistently shown that fMRI activity in rlPFC tracks explicit confidence estimates (11,(14)(15)(16), and that the microstructure of rlPFC can predict the degree to which an individual's subjective evaluations reflect objective performance (36)(37)(38). One hypothesis, which may reconcile these results with ours, is that rlPFC is not itself involved in computing a probability that a choice is correct, but instead governs the mapping of internal onto explicit confidence estimates.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is supporting
confidence: 78%
“…Previous studies have consistently shown that fMRI activity in rlPFC tracks explicit confidence estimates (11,(14)(15)(16), and that the microstructure of rlPFC can predict the degree to which an individual's subjective evaluations reflect objective performance (36)(37)(38). One hypothesis, which may reconcile these results with ours, is that rlPFC is not itself involved in computing a probability that a choice is correct, but instead governs the mapping of internal onto explicit confidence estimates.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is supporting
confidence: 78%
“…We omitted all trials from the first block to ensure staircase stabilisation, similar to previous studies (Fleming et al, 2010, 2012; Allen et al, 2017; Hauser et al, 2017). Trials with early (<100 ms), late (>1500 ms) or missing responses were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…information coded in the dACC to the anterior PFC (Allen et al, 2017;Fleming et al, 2010Fleming et al, , 2014McCurdy et al, 2013), whereas accurate memorial metacognition is dependent on memory-mediated regions such as the medial PFC, mid/posterior cingulate cortex, inferior parietal lobule (IPL) and precuneus (Baird et al, 2013;Chua et al, 2006;McCurdy et al, 2013;Simons et al, 2010;Ye et al, 2018).…”
mentioning
confidence: 99%